2020
DOI: 10.1101/2020.10.07.20208645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low zinc levels at clinical admission associates with poor outcomes in COVID-19

Abstract: Background: Biomarkers to predict Coronavirus disease-19 (COVID-19) outcome early at infection are urgently needed to improve prognosis and treatment. Zinc balances immune responses and also has a proven direct antiviral action against some viruses. Importantly, zinc deficiency (ZD) is a common condition in elderly and individuals with chronic diseases, two groups with more severe COVID-19 outcomes. We hypothesize that serum zinc content (SZC) influences COVID-19 disease progression and thus might represent a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…When zinc level <80 μg/dL was defined as deficiency, 57.4% of patients were deficient in zinc, and they had higher rates of complications, prolonged hospitalization, and increased mortality. Vogel-González et al [ 166 ] also measured serum zinc of COVID-19 patients admitted to the hospital. Serum zinc levels lower than 50 μg/dL at admission correlated to worse clinical presentation, longer time to reach stability, and higher mortality.…”
Section: Possible Mechanisms Of Gustatory Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…When zinc level <80 μg/dL was defined as deficiency, 57.4% of patients were deficient in zinc, and they had higher rates of complications, prolonged hospitalization, and increased mortality. Vogel-González et al [ 166 ] also measured serum zinc of COVID-19 patients admitted to the hospital. Serum zinc levels lower than 50 μg/dL at admission correlated to worse clinical presentation, longer time to reach stability, and higher mortality.…”
Section: Possible Mechanisms Of Gustatory Dysfunctionmentioning
confidence: 99%
“…They also found the expression in human salivary glands of metabotropic zinc receptor/G-protein-coupled receptor (ZnR/GPR39) that modulates saliva secretion from submandibular glands. Since many COVID-19 patients show lower serum zinc concentrations [ 165 , 166 ], zinc deficiency may contribute to xerostomia associated with COVID-19.…”
Section: Possible Mechanisms Of Xerostomiamentioning
confidence: 99%
“… Calder, 2020 Calder et al, 2020 Celik et al, 2021 Chaturvedi et al, 2004 Culbertson and Culotta, 2021 de Almeida Brasiel, 2020 de Jesus and de Araú jo Andrade, 2020 Ersö z and Y ı lmaz, 2021 Grzywa-Celiń ska et al, 2020 Hultman and Pollard, 2015 Moghaddam et al, 2020 Muhammad et al, 2021 Rahman and Idid, 2021 Skalny et al, 2020 Vogel-Gonzá lez et al, 2021 Zeng et al, 2021 .…”
Section: Uncited Referencementioning
confidence: 99%
“…5 31 32 In summary, zinc has direct antiviral properties against SARS-CoV-2 and other coronaviruses. 31-33 There is the potential for broader multisystem effects via modulation of angiotensin converting enzyme 2 activity, inflammation, immunity, haemostasis and hypoxic responses. 5 31 32 34 Further, the risk factors for severe illness from SARS-CoV-2 infection, such as increasing age, obesity and chronic disease, are also risk factors for zinc deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…5 32 35 Observational studies conducted in Germany, Spain, Japan and Iran have reported that lower baseline zinc levels in hospitalised adults were associated with a higher risk of mortality, severe illness, complications, and longer hospital stay following SARS-CoV-2 infection. 33 36-38…”
Section: Introductionmentioning
confidence: 99%